Enucleação em paciente felino doméstico - Souza, Karlany Silva (Universidade Federal do Tocantins, 2023)
This report aims to describe the activities carried out throughout the supervised mandatory curricular internship, held at the Clínica Veterinária Universitária, in the city of Araguaína - TO, during the period from March 7 to May 16, 2022, in the areas of Clinic and Surgery. of Small Animals, under the supervision of the veterinarian Daiane Michele Frantz and guidance of Professor Drª Laiane Teixeira Sousa Moura, totaling 390 hours. During the internship, 142 consultations were followed, 46 of which were surgeries, 1 euthanasia, 26 imaging exams, 29 outpatient procedures and 67 returns. This report contains the description of the internship location, as well as its infrastructure, activities developed, casuistry in the medical and surgical clinic sectors, proceeding with the description of a case of Enucleation in a feline patient, selected to be reported and discussed.